Hubungan Gaya Kepemimpinan dan Iklim Organisasi di Lingkungan Sekretariat Daerah Kabupaten Sidenreng Rappang - Hamidong Hamidong (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
This research was conducted at Secretariat District Office of Sidenreng Rappang Regency, arguing several interesting phenomenons to study, primarily in terms of leadership style. The goals of this research was to provide an overview of the relationship between leadership style and organizational climate at Secretariat District Office of Sidenreng Rappang Regency, along with the influencing factors. Data collection methods used in this research were (1) Observation, (2) Interview , (3) Questionnaire, and (4) Library research. The collected data was analyzed using frequency tables and percentages. The population in this research took 158 people, and 32 of them accounted as samples. The results showed that relationship between leadership style and organizational climate at Secretariat District Office of Sidenreng Rappang Regency was good, consisting directive, consultative, and participatory, which gained 80%.